Interference of medicines in laboratory exams - Silva,Raquel S. (2021)
ABSTRACT Objective: Conduct a survey on the interference of drugs in laboratory tests. Methodology: To identify the interference of each medication in laboratory tests, the Municipal List of Essential Medicines (Remume) of a medium-sized municipality in the state of Minas Gerais was used along with the following sources of information: Dynamed, Micromedex® and Nursing Reference Center. Results: We observed that the majority (67.7%) of Remume drugs can interfere in one or more laboratory tests; among them, the main classes of drugs are diuretics, beta blockers, ß-lactams, sulfonamides, macrolides, tricyclic antidepressants and selective serotonin reuptake inhibitors antidepressants. Conclusion: It is extremely important to disseminate knowledge about these interferences so that health professionals are alert and know how to identify the possible changes, reducing analytical errors and subsequently misdiagnosis and erroneous monitoring. Continued education on drug interference in laboratory tests is equally important.